Role of feedback on English academic writing skills of tertiary level Iraqi English as a foreign language EFL students: a review of literature - Algburi, Entesar A.; Razali, Abu Bakar (Human Resource Management Academic Research Society, 2022)
Recent studies have shown that Iraqi English as a foreign language (EFL) students face many challenges when composing in an academic context, where they produce a wide range of errors in spelling, punctuation and grammar, and they have trouble writing coherent texts and managing their writing tasks (Alshujairi, 2017; Ahmed & Mohammed, 2015). One of the main reasons why Iraqi EFL students lack proficiency in their academic writing is that they do not receive the necessary feedback to improve their writing. The idea of feedback as a crucial aspect for improving teaching writing instruction and improving academic writing acquisition has not been given much attention in EFL Iraqi literature. This issue is quite problematic because mainstream EFL writing instructors need to equip themselves with effective instructional techniques and strategies to improve EFL student writers’ skills. Thus, this article reports on the review of studies on feedback for ESL Iraqi undergraduate students. This review sheds light on the relationship between providing feedback, improving academic writing skills and offering guidelines for writing instructors to help EFL Iraqi undergraduate students improve their academic writing. Furthermore, this review hopes to urge administrators in higher education to provide feedback courses to enhance writing instructors’ feedback knowledge. Finally, this literature review hopes to explore gaps in the Iraqi EFL literature context, which should be adequately addressed in future research studies.